WHO Expert Committee on specifications for pharmaceutical preparations : fortieth report. (Geneva, Switzerland : World Health Organization, 2006)
This report presents the recommendations of an international group of experts convened by the World Health Organization to consider matters concerning the quality assurance of pharmaceuticals and specifications for drug substances and dosage forms. Annexes include: a list of available international chemical reference substances and international infrared spectra; supplementary guidelines on good manufacturing practices for heating, ventilation and air-conditioning systems for non-sterile pharmaceutical dosage forms; updated supplementary guidelines on good manufacturing practices for the manufacture of herbal medicines; supplementary guidelines on good manufacturing practices for validation; good distribution practices for pharmaceutical products; a model quality assurance system for procurement agencies (recommendations for quality assurance systems focusing on prequalification of products and manufacturers, purchasing, storage and distribution of pharmaceutical products); multisource (generic) pharmaceutical products: guidelines on registration requirements to establish interchangeability; a proposal to waive in vivo bioequivalence requirements for WHO Model List of Essential Medicines immediate-release, solid oral dosage forms; and additional guidance for organizations performing in vivo bioequivalence studies.
Introduction -- General Policy -- Quality control- specifications and tests -- Quality control- international Reference Materials -- Quality control- national laboratories -- Quality assurance- Good Manufacturing Practices -- Quality assurance- inspection -- Quality assurance- distribution -- Quality assurance- risk analysis -- Quality assurance- stability -- Prequalification -- Regulatory guidance on interchangeability for multisource (generic) pharmaceutical products -- Donations of medicine
Includes bibliographical references.
Keywords: DRUG QUALITY CONTROL